P02.07 Utilisation of risk score tool of internet i want the kit (iwtk) home self-collection program for sexually transmitted infections (stis) in males. (13th September 2015) - Hsieh, Y-H; Jett-Goheen, M; Dize, L; Barnes, M; Barnes, P; Gaydos, CA
Abstract : Introduction: In our previous pilot study on the internet I Want The Kit (IWTK) home self-collection program for sexually transmitted infections (STIs), a voluntary risk score tool predicted STIs well for the female volunteers but not for the males. We investigated the association of IWTK risk score and the presence of STIs in male users when the risk score quiz became mandatory for the program. Methods: A six-question quiz which includes demographic and sexual risk behaviour became a mandatory part of IWTK in August 2103. This analysis was restricted to male participants living in Maryland and Washington DC using IWTK August 2013–April 2015. Cochran-Armitage trend test was performed to determine if the prevalence of STIs (chlamydia, gonorrhoea, or trichomonas infection) increased with the higher score of risk score category. Results: Overall, 592 male participants submitted specimens for STI testing and completed risk score quizzes. The majority (57%) were < 30 years (mean: 30.1 ± 9.3 years); 42% white, 42% black, and 16% other races. 203 (34.3%) resided in zip codes of Baltimore City. The majority (53%) of the participants had risk score of 4–6, followed by scores of 0–3 (25%), and  7–10 (22%). The overall prevalence of STIs was 10.5% (62/592). The prevalence of STIs was 6.2% for users with risk score of 0–3, 10.9% for those with 4–6, and 14.3% for those with  7–10 (trend test: p = 0.026). 52% (13/25) of STI positive participants resided in three zip codes located in central and northeast Baltimore City and participants in these three zip codes had a marginally higher risk score than others (p = 0.082). Conclusions: After excluding potential selection bias, IWTK risk score tool predicted the presence of STIs for male users and could potentially be used for identifying hotspots for STI intervention. Disclosure of interest statement: The research group has received research funding from U54EB007958, NIBIB, NIH; AI068613–01, NIH, NIAID.